2004
DOI: 10.1001/archopht.122.5.705
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postoperative Use of a Topical Agent to Prevent IntraocularPressure Elevation After Pars Plana Vitrectomy With Gas Tamponade

Abstract: To determine whether a single topical aqueous suppressant applied immediately after pars plana vitrectomy with long-acting gas tamponade prevents intraocular pressure (IOP) elevation. Methods: Fifty patients who met the inclusion criteria and underwent pars plana vitrectomy with long-acting gas tamponade were randomized to receive a combination of timolol maleate and dorzolamide hydrochloride, long-acting timolol alone, dorzolamide alone, or placebo at the conclusion of surgery. The IOP was checked by a portab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
(18 reference statements)
0
19
0
1
Order By: Relevance
“…In patients undergoing combined vitrectomy and cataract surgery, IOP at 5 h was not associated with any parameter but at 1 day was significantly associated with circumferential dimension of retinal tears (P \ 0.05). [6] report that 75% of patients showed an IOP of C25 mmHg at 5 h after vitrectomy for RD. In our study, the incidence of IOP elevation was higher at 1 day than at 5 h postoperatively.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In patients undergoing combined vitrectomy and cataract surgery, IOP at 5 h was not associated with any parameter but at 1 day was significantly associated with circumferential dimension of retinal tears (P \ 0.05). [6] report that 75% of patients showed an IOP of C25 mmHg at 5 h after vitrectomy for RD. In our study, the incidence of IOP elevation was higher at 1 day than at 5 h postoperatively.…”
Section: Resultsmentioning
confidence: 98%
“…If a severe pressure spike develops, postoperative vision can be damaged, even after an otherwise successful vitrectomy [10]. Previous studies show that postoperative IOP spikes may be blunted by using prophylactic topical aqueous suppressants [5,6]. Topical prophylactic therapy may be considered in patients susceptible to IOP elevation or in eyes with higher risks of pressure rise, such as large size of retinal tears and long history of retinal detachment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al 15 found that 4.8% of 89 patients undergoing 20G vitrectomy prophylactic anti-glaucoma medication was not used in either of these two studies, despite evidence in the literature that topical agents can be effective at preventing, or at least attenuating, the IOP spike. 13,14 In contrast, the study by Cochrane et al 16 of 81 patients undergoing 23G vitrectomy advocates the abandonment of the day-1 visit. The authors checked the IOP immediately postoperatively and found no patients with an IOP 430 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of high IOP at day 1 varies between 6 and 67%. [9][10][11][12] However, numerous groups have suggested that prophylactic topical treatment with apraclonidine 13 , dorzolamide, and/or timolol 14 are effective at preventing IOP spikes.…”
Section: Introductionmentioning
confidence: 99%